Financial insecurity and risk experiences of justice involved persons with severe mental illness. Issue 6 (2nd November 2017) - Cuddeback, Gary S.; Blank Wilson, Amy; Despard, Mathieu R.; Tomar, Nikhil; Chowa, Gina
ABSTRACT: More information is needed about the financial experiences of justice-involved persons with severe mental illness. Qualitative and quantitative methods were used to examine the financial resources, financial risk experiences, and financial literacy of a random sample of 12 mental health court participants. Mental health court participants had limited financial resources, frequently ran out of money, and had engaged very few financial tools to manage their money. Justice-involved persons with severe mental illness need financial management interventions to help develop strategies for managing depleted resources and to develop the financial resources needed to live in community settings.